2020
DOI: 10.1007/s00520-020-05709-1
|View full text |Cite
|
Sign up to set email alerts
|

Multinational Association of Supportive Care in Cancer (MASCC) 2020 clinical practice recommendations for the management of immune checkpoint inhibitor endocrinopathies and the role of advanced practice providers in the management of immune-mediated toxicities

Abstract: Immune checkpoint inhibitors (ICIs) have emerged as the newest pillar of cancer treatment, transforming outcomes in melanoma and showing benefit in a range of malignancies. Immune-mediated toxicities, stemming from increased activity within the T cell lineage, range from asymptomatic or mild complications to those that are fulminant and potentially fatal. Immune-mediated endocrinopathies include hypophysitis, thyroiditis, and insulin-dependent diabetes mellitus. These presentations, which may be vague and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The increasing trend of incidence of ICI-TDs may be explained by a more profound and prevalent understanding of the disease by both oncologists and endocrinologists. In a recent couple of years, patients on ICIs therapy were arranged for regular surveillance of thyroid function by the oncologists along with the latest published guidelines for ICI therapy, 7 which may contribute to the increasing diagnosis rate of ICI-TDs by reporting years. Due to the decreasing prescription of anti-CTLA-4 (ipilimumab) mono-therapy and more frequent application of anti-PD-1 + anti-CTLA-4 therapy, the incidence of anti-CTLA-4 mono-therapy induced thyroid dysfunction reduced over time.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trend of incidence of ICI-TDs may be explained by a more profound and prevalent understanding of the disease by both oncologists and endocrinologists. In a recent couple of years, patients on ICIs therapy were arranged for regular surveillance of thyroid function by the oncologists along with the latest published guidelines for ICI therapy, 7 which may contribute to the increasing diagnosis rate of ICI-TDs by reporting years. Due to the decreasing prescription of anti-CTLA-4 (ipilimumab) mono-therapy and more frequent application of anti-PD-1 + anti-CTLA-4 therapy, the incidence of anti-CTLA-4 mono-therapy induced thyroid dysfunction reduced over time.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, pharmacological dose of glucocorticoids is used as first-line therapy for treatment of irAEs. However, in terms of ICI-related hypophysitis, it is recommended to use physiological doses of glucocorticoids as a replacement therapy unless the presence of severe visual disturbance or intolerable headache because pharmacological dose of glucocorticoids does not restore pituitary function and recent study suggested high-dose glucocorticoids in patients with ICI-related hypophysitis might impair the effect of ICIs and survival [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term hormone replacement therapy is therefore necessary. 1,5 Lichen and autoimmune thyroid disorders are more frequent in females, and some data suggest they share genetic risk. Thus, their co-occurrence in some patients could be explained by a common pathogenic mechanism.…”
Section: E396 |mentioning
confidence: 99%